Lorsque le tourisme se préoccupe de la pauvreté - Olivier Dehoorne; Corina Tatar; Sopheap Theng (Études Caribéennes)
Political declarations and manuals to combat poverty occur while poverty is sustainable within our society. Then, economic and political leaders consider tourism as a tool for poverty reduction. Policies that judiciously use tourism must allow a catch-up in favor of the poorest.The article emphasizes the complexity of tourism and the need to take into account the tourism project in its entirety. The host territory is the support for tourist consumption which require specific improvements. But the distribution of revenues from tourism, the international movement and the final distribution of the profits must be considered across all local, national and international actors involved in the field of tourism.